Information about adverse drug reactions reported in children: a qualitative review of empirical studies - Aagaard, Lise (Blackwell Science Inc, 2010)
AIM: To review the literature on adverse drug reactions (ADRs) in children with respect to occurrence, seriousness, type, therapeutic group, age and gender of the child and category of reporter. METHODS: Medline and Embase databases were searched from origin and updated until February 2010. We included empirically based articles on ADRs in populations aged 0 to 17 years. Studies monitoring ADRs in patients with particular conditions or drug exposure were excluded. We extracted information about types and seriousness of ADRs, therapeutic groups, age and gender of the child and category of reporter. ADR occurrence was calculated as incidence rate and prevalence. RESULTS: We included 33 studies monitoring ADRs in general paediatric populations. The highest numbers of ADRs were reported in national ADR databases where data were collected over a longer period than in studies monitoring inpatients and outpatients. However, prevalence and incidence were much lower in the national databases. Types of reported ADRs, seriousness of ADRs and types of medicines differed substantially between studies due to differences in time periods and patient populations. Information about ADRs was mainly provided by health care professionals, although parents also contributed reports. CONCLUSIONS: We found a higher incidence rate of ADRs in hospitalized children and outpatients than in national databases. There seems to be considerable potential for increasing the knowledge of ADRs by advocating the submission of reports to the spontaneous reporting systems. Our study underscores that ADRs in children constitute a significant public health problem.